Hierarchical self-assembly of a small monomer with two orthogonal binding sites: from discrete hexagonal containers to a stimuli-responsive supramolecular gel. Issue 5 (3rd June 2018) - Grossert, Kerstin; Sicking, Wilhelm; Zellermann, Elio; Schmuck, Carsten
Abstract: A small self-complementary monomer1 is described, with two orthogonal binding interactions based on ion pairing and metal-ligand coordination, which is reversibly switchable between monomer, cyclic oligomers as well as linear- and 3D-netlike polymers in polar solution (DMSO). The aggregation was studied by atomic force microscopy, transmission electron microscopy, helium ion microscopy (HIM) and diffusion ordered spectroscopy (DOSY NMR). First, at lower concentrations, hexagonal cyclic containers are formed, whereas at higher concentrations hierarchical self-assembly leads to a metallogel. This gel can be switched between the sol/gel-state using different stimuli like pH, temperature changes or the addition of metal and metal-chelators, respectively. The supramolecular gel is rather stable and shows interesting shear thinning behavior. Abstract :